AI transforming horticulture: A glimpse into the future - Rajan, Shailendra (Indian Horticulture, 2025)
The horticulture industry has witnessed transformative advancements, especially with the integration of artificial intelligence (AI), which is reshaping farming practices through data-driven precision agriculture. AI enables the collection and analysis of vast data volumes related to soil conditions, climate, and pest patterns, facilitating real-time, optimized decision-making for farmers. This approach enhances efficiency by tailoring pest control, fertilization, and irrigation schedules, which improves productivity, reduces resource waste, and increases sustainability. Key applications of AI in horticulture include niche modeling for crop diversification, variety selection based on regional adaptability, and the extension of crop cycles to previously unsuitable regions. Furthermore, AI aids in addressing climate change by projecting region-specific crop viability, thus allowing farmers to adapt proactively. Additional areas of impact include urban farming, yield prediction, quality control, and niche market targeting. AI also contributes to restoring degraded lands by analyzing soil health and environmental conditions to support suitable cropping strategies. As AI evolves, its applications will advance toward holistic environmental management, equipping farmers to mitigate climate change impacts and supporting sustainable agricultural growth.